PENDAPATAN DAN EFISIENSI USAHA TANI JAGUNG MANIS (Zea mays saccharata Sturt) DI DESA TANJUNG AGUNG KECAMATAN SEGINIM KABUPATEN BENGKULU SELATAN: - - Sarina sarina sarina (UNIVERSITAS LANCANG KUNING, 2018)
Abstrack The purpose of this research is to know the income and efficiency of sweet corn farm in Tanjung Agung Village, Seginim District, South Bengkulu Regency. The study was conducted in Tanjung Agung Village, Seginim District, South Bengkulu Regency from July 2016 to September 2016. The method used is simple random sampling method. Total population taken is 20% that is 24 people from 120 farmers sweet corn. The data used are primary data and secondary data. Data were analyzed descriptively and quantitatively. Data analysis method used in this research is analysis of production cost, revenue, income and R / C ratio. Based on the results of research on Sweet Maize Farming in Tanjung Agung Village, Seginim District of South Bengkulu Regency, its known that the average income earned by farmers with land area of ​​0.45 ha is Rp Rp 7,511,225 / ut / ut. The R / C ratio is 3.24 indicating that sweet corn farming is efficient or profitable.